The Rosetta Stone Thai level 1 - Fairfield Language Technologies (Firm) (Harrisonburg, VA : Fairfield Language Technologies, 2002)
A comprehensive language learning solutions for private, educational and professional use. With complete curriculum management, networking and record-keeping capabilities
Keywords: Thai language -- Study and teaching -- Foreign speakers; Thai language